Unravelling the nuances: A scoping review on fatherhood and men’s participation in antenatal care in rural Sub-Saharan Africa - Anthony Shuko Musiwa; Webster Mavhu; Owen Nyamwanza; Agatha Nyambi; Maya Stevens-Uninsky; Nadia Rehman; Naharin Sultana Anni; Roseline Dzekem Dine; Elizabeth Chadambuka; Rachel Couban; Lawrence Mbuagbaw (PLoS ONE, 2025)
Introduction Men’s participation in antenatal care (ANC) in sub-Saharan Africa (SSA) is shaped by diverse conceptions and experiences of fatherhood. However, most discussions rely on biomedical models that typically view men’s participation narrowly as a strategy to increase ANC uptake in mainstream health facilities, often marginalizing culturally specific forms of participation. We aimed to consolidate the existing literature on the complex nuances of how attitudes, knowledge, variations in involvement, and decision-making dynamics influence men’s participation in ANC in rural SSA. Methods Following the scoping review methodology developed by Arksey and O’Malley, we searched ten databases (African Index Medicus, Africa Journals Online, CINAHL, Cochrane Library, EMBASE, MEDLINE/PubMed, PsycINFO, Sociology Collection, Social Sciences Abstract, Social Sciences Citation Index) for peer-reviewed articles published between January 1st, 2000, and October 31st, 2024. We included only studies that systematically analyzed primary or secondary data to examine fatherhood and men’s participation in ANC in a rural setting in SSA. We applied no language restrictions. Results We identified 7665 articles, full-text reviewed 797 articles, and included 77 articles that reported 58 qualitative, 6 quantitative, and 13 mixed-methods studies conducted in 15 SSA countries. We identified nine themes under three categories addressing our review’s objective: 1) three themes described men’s attitudes and knowledge around participating in ANC; 2) four themes depicted variations in men’s participation in ANC throughout pregnancy; and 3) two themes described how men’s participation in ANC was shaped by largely collaborative communal decision-making structures in rural SSA. Conclusion While heterogeneous, the existing body of evidence highlights contextually-valid and socioculturally meaningful nuances that reflect the lived realities of fatherhood and men’s participation in ANC across rural SSA. Policymakers and practitioners should leverage these nuances as strengths, and further research should employ Afrocentric approaches to better understand these issues.